Treatment of human life in phenomenology and existentialism in context of the modern philosophy of history - Kusherets, Tamara (Actual Problems of Mind, 2017)
The paper introduces the idea of overcoming of naturalism and fatalism in the modern Ukrainian philosophy of history by taking into account some results of existential-phenomenal philosophy. The author claims that her approach makes it possible to represent a human being as a real historical subject.